2020
DOI: 10.4085/1062-6050-0547.19
|View full text |Cite
|
Sign up to set email alerts
|

Sport Specialization and Low Bone Mineral Density in Female High School Distance Runners

Abstract: Context Sport specialization may contribute to sport injury and menstrual dysfunction in female high school distance runners. Despite the recent growth in sport specialization, including among high school–aged runners, the association of sport specialization with bone mineral density (BMD) remains poorly described. Objective To evaluate whether sport specialization was associated with BMD in female high school distance runner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The lower lumbar spine aBMD in RUN compared with reference data possibly reflects the systemic demands of distance running in terms of its impact on energy availability and circulating hormone levels. Twenty-one percent (3 of 14) of participants (19), who reported that high school distance athletes who highly specialized in running (i.e., participation in distance running only and for ≥9 months•yr −1 ) were five times more likely to have low aBMD compared with low sport specializers (≥1 nonrunning sport and distance-running sport/s for ≤8 months•yr −1 ). Lower whole-body bone mass and lumbar spine aBMD have prospectively been shown to be predictive of BSI in female athletes (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower lumbar spine aBMD in RUN compared with reference data possibly reflects the systemic demands of distance running in terms of its impact on energy availability and circulating hormone levels. Twenty-one percent (3 of 14) of participants (19), who reported that high school distance athletes who highly specialized in running (i.e., participation in distance running only and for ≥9 months•yr −1 ) were five times more likely to have low aBMD compared with low sport specializers (≥1 nonrunning sport and distance-running sport/s for ≤8 months•yr −1 ). Lower whole-body bone mass and lumbar spine aBMD have prospectively been shown to be predictive of BSI in female athletes (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, a focus on running activities when younger, at the expense of participating in other sports, may also play a role. Female high school distance runners who highly specialized in distance running (running >9 months·yr −1 with no participation in other sports) were found to have lower spine aBMD than those who did not specialize (19).…”
mentioning
confidence: 97%
“…Low BMD has earlier been observed in long-distance runners, despite competing in a weight-bearing sport. [10][11][12][13][14] Most studies have focused on elite adolescent runners 12 13 or adult runners below the elite level. 11 Barrack et al 12 observed low BMD (Z-score <−1) in 39.8% of female adolescent runners.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Low BMD has earlier been observed in long-distance runners, despite competing in a weight-bearing sport 10–14. Most studies have focused on elite adolescent runners12 13 or adult runners below the elite level 11. Barrack et al 12 observed low BMD (Z-score <−1) in 39.8% of female adolescent runners.…”
Section: Introductionmentioning
confidence: 99%
“…Young wrestling/judo participants and sprinters have been identified as having higher BMD than endurance athletes and swimmers, and those who are inactive [56][57][58]. A low BMD has been associated with adolescents who have specialised early into endurance running [59], and risk factors for low BMD in male adolescent runners include body weight < 85 % expected, weekly mileage > 30 miles, history of stress fracture and less than one serving of calcium per day [60]. Horse racing is a weight restricted sport and 29 % of entry level male flat jockeys (mean age 18.5 years) were identified as Review Thieme having Z scores < 2 [61], compared to 13 % of male jump jockeys where the weight restriction is less.…”
Section: Bone Mineral Density (Bmd) and Achieving Peak Bone Mass (Pbm)mentioning
confidence: 99%